(untitled) (Bangladesh Journal of Animal Science, 2013)
The present study was conducted to evaluate the effect of different levels of methionine supplementation on feed intake, nutrient digestibility and growth performance of growing rabbit. Sixteen weaned crossbred New Zealand White (NZW) growing rabbits (30-35 d) were distributed into four treatment groups having four replications in each group using a Completely Randomized Design (CRD). Basal diet composed of green grass (dhal grass) and concentrate mixture which was offered ad libitum basis for 56 days period. Four levels of methionine such as 0.0% (control), 0.15%, 0.25%, and 0.35% were supplemented randomly to rabbits. Results showed that supplementation of methionine did not affect green grass intake. Cumulative as well as daily concentrate and DM intake were significantly (p<0.05) higher for all methionine groups than control group. Final body weight gain as well as daily, weekly and cumulative body weight gains were improved significantly with increasing level of methionine. It was found that methionine had significant (p<0.01) effect on digestibility of DM, CP, NFE and EE but CF digestibility did not differ significantly. Digestibility was improved with increasing the level of methionine. Feed conversion ratio also decreased significantly with methionine supplementation, and 0.25% methionine group showed the best performance among the four treatments. DOI: http://dx.doi.org/10.3329/bjas.v42i1.15777 Bang. J. Anim. Sci. 2013. 42 (1): 40 43